Elaboración de biopelículas de harina de Musa Acuminata activadas con aceites esenciales Rosmarinus Officinalis Y Eucalyptus Globulus mediante técnica casting - Bonifaz Ramos, Evelyn Jeaneth (2021)
In Ecuador there is a large amount of plastic waste that is not properly managed for its degradation, so this experimental study was carried out for the elaboration of biofilms based on banana flour activated with essential oil of rosemary (Rosmarinus officinalis) and essential oil eucalyptus (Eucalyptus globulus) using the Casting technique; as an alternative to replace synthetic polymers. Six treatments (AEE1, AEE2, AEE3, AER4, AER5, AER6) were elaborated at different concentrations of essential oils, mechanical physical analyzes (pH, moisture content, water resistance, thickness) were performed in triplicate, statistically determining the best formulation. Finally, it concluded that the AEE3 treatment presented better properties, a moisture content of 0.12%, a pH of 7.12; regarding the mechanical analysis of resistance to water, it showed a maximum time of 17.33 min and a thickness of 0.31 mm. According to the financial evaluation, the project is feasible for its execution and elaboration of biodegradable packaging for nuts; its financial indicators are favorable and its cost benefit is $ 1.26, it earns $ 0.26 ctvs. for every dollar invested in packaging.